European Code against Cancer 4th Edition: Breastfeeding and cancer. (December 2015) - Scoccianti, Chiara; Key, Timothy J.; Anderson, Annie S.; Armaroli, Paola; Berrino, Franco; Cecchini, Michele; Boutron-Ruault, Marie-Christine; Leitzmann, Michael; Norat, Teresa; Powers, Hilary; Schüz, Joachim; Wiseman, Martin; et al.
Abstract: Breast cancer is the most frequent cancer in women, and incidence rates have been rising in European Union (EU) countries over recent decades due in part to a sharp decline in breastfeeding practices. Evidence for a protective association between breastfeeding and the risk of breast cancer at all ages is convincing, and modest protective relationships between breastfeeding and the risk of endometrial and ovarian cancers have been suggested. The reduction in breast cancer risk is estimated at 2% for an increase of 5 months of lifetime breastfeeding. The longer women breastfeed, the more they are protected against breast cancer. In addition, breastfeeding is associated with several health benefits for both the mother and the breastfed child. Taking all this evidence into account, the 4th edition of the European Code against Cancer recommends: "Breastfeeding reduces the mother's cancer risk. If you can, breastfeed your baby".